New Records of Distribution for Protomydas coerulescens (Olivier) (Diptera: Mydidae) - Krolow, Tiago Kütter; Vieira, Rodrigo (EntomoBrasilis, 2016)
Abstract. This paper provide the first record of Protomydas coerulescens (Olivier) for states of Amazonas, Rôndonia and Tocantins, Brazil. Previously, this species was recorded in Colombia and Brazil (Pará, Mato Grosso, Minas Gerais, São Paulo and Rio de Janeiro). Illustration and map of distribution of P. coerulescens are provided. Novos registros de distribuição de Protomydas coerulescens (Olivier) (Diptera: Mydidae) Resumo. Este trabalho fornece os primeiros registros de Protomydas coerulescens (Olivier) para os estados brasileiros do Amazonas, Rondônia e Tocantins, Brasil. Esta espécie possuía registros prévios para Colômbia e Brasil (Pará, Mato Grosso, Minas Gerais, São Paulo e Rio de Janeiro). Aqui são fornecidos ilustrações e um mapa atualizado dos registros de distribuição de P. coerulescens.